EMPOWERMENT OF THE KLAYILI FOREST FARMERS GROUP (KTH) IN MAKING AGARWOOD TEA IN KLAYILI VILLAGE, KLAYILI DISTRICT, SORONG REGENCY: PEMBERDAYAAN KELOMPOK TANI HUTAN (KTH) KLAYILI DALAM PEMBUATAN TEH GAHARU DI KAMPUNG KLAYILI DISTRIK KLAYILI KABUPATEN SORONG - Azis Maruapey; Lona Helti Nanlohy; Fajrianto Saeni; Sanny Hahury; Rajab Lestaluhu (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
Agarwood plants have been used more parts of the stem which contains high economic value sapwood. However, it turns out that gaharu leaves have the potential to be developed as a source of natural antioxidant compounds so that they can be made into herbal teas that are healthy, safe and suitable for consumption. This workshop is an effort to empower the Klayili Forest Farmers Group (KTH) in Sorong Regency to process agarwood leaf into herbal tea drinks. The method of implementing this Community Service (PkM) activity is a workshop focused on community empowerment efforts through Forest Farmers Groups in making tea from agarwood leaf. Implementation of Community Service (PkM) is carried out in the form of workshops with practical demonstrations. The results of Community Service (PkM) activities in the form of Empowerment of the Klayili Forest Farmer Group (KTH) in the Production of Herbal Tea Made from Agarwood Raw Materials in Klayili Village include among others: 1. Inter-competent preparation and coordination stage; 2). Preparation of facilities and infrastructure for making gaharu tea; and 3). The process of making gaharu tea, which includes taking raw materials, sorting leaves, cleaning leaves, drying, chopping, blending, oxidation of leaves, and packaging. Based on the results of the activity, there was an increase in understanding related to the procedure for making gaharu tea starting from preparation, processing and packaging